Orkestralna dela Marijana Lipovška - bibliografski popis in oris - Florjanc, Ivan (Glasbenopedagoški zbornik (Ljubljana), 2011)
The author outlines the image and mind of Marijan Lipovšek through extensive citations from the composer's writings. Along the lines of hermeneutics that is a good key to the issues related to the composer's orchestral creativity. A bibliographic list comprising all Lipovšek's orchestral works (including unfinished) as well as compositions for solo and orchestra is followed by an analytical outline of the most important and completed creations (Simfonija, three Suites, symphonic poem Domovina, Toccata quasi aperture and three concerts). In the article other Lipovšek's works are also mentioned, as well as music he composed for film.
Keywords: 20.st.; 20th century; bibliografije; bibliography; glasbena analiza; Lipovšek, Marijan; music analysis; orchestral music; orkestralna glasba; Slovenia; Slovenian music; Slovenija; slovenska glasba; slovenski skladatelji